1996
DOI: 10.1002/jbmr.5650110704
|View full text |Cite
|
Sign up to set email alerts
|

Amelin: An enamel-related protein, transcribed in the cells of epithelial root sheath

Abstract: Since 1974, when Slavkin and his collaborators proposed the epithelial origin of cementum, many experiments have been carried out to provide evidence for deposition of enamel-related proteins along the root surface. However, neither amelogenin nor other proteins have fully satisfied expectations. In previous studies, we have identified a novel mRNA coding for an extracellular-like protein which we called amelin. It was expressed at high levels in secretory and postsecretory ameloblasts in rat molars and inciso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(40 citation statements)
references
References 15 publications
1
37
0
Order By: Relevance
“…35 Ameloblastin was cloned from an enamel protein in rat incisor tooth germs. 4,7,18 Sheathlin, considered to be part of the same protein as ameloblastin, was recently cloned from porcine tooth germs. 16 An immunohistochemical study using antibodies that recognize different regions of that protein showed that sheathlin is synthesized by ameloblasts and secreted into the immature enamel matrix with posttranslational and postsecretory modifications and that cleaved NH 2 -terminal polypeptides concentrate in the prism sheath.…”
Section: Discussionmentioning
confidence: 99%
“…35 Ameloblastin was cloned from an enamel protein in rat incisor tooth germs. 4,7,18 Sheathlin, considered to be part of the same protein as ameloblastin, was recently cloned from porcine tooth germs. 16 An immunohistochemical study using antibodies that recognize different regions of that protein showed that sheathlin is synthesized by ameloblasts and secreted into the immature enamel matrix with posttranslational and postsecretory modifications and that cleaved NH 2 -terminal polypeptides concentrate in the prism sheath.…”
Section: Discussionmentioning
confidence: 99%
“…Ameloblastin (AMBN), also known as sheathlin or amelin, is the most abundant nonamelogenin enamel matrix protein (4,5,14) and a member of the secretory calcium-binding phosphoprotein (SCPP) gene cluster of evolutionarily related molecules that regulate skeletal mineralization (13). Further, AMBN induces cell attachment, proliferation, and differentiation of periodontal ligament cells in vitro (34).…”
mentioning
confidence: 99%
“…4, 5). Fong et al 17) showed that enamel-related proteins such as amelin were associated with root formation in rats. Tokiyasu et al 18) showed that the enamel matrix derivative activated cementoblasts in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%